2019
DOI: 10.1039/c9nj01039d
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of rutin with the oxidovanadium(iv) cation. Anticancer improvement effects of glycosylated flavonoids

Abstract: This work reports the biological evaluation of the new complex Na2[VO(rut)(OH)2]·5H2O (rut = rutin, a glycosylated flavonoid).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Metal-flavonoid chelates have a considerably better biological activity than their flavonoid and metal precursors on their own and we have reported this behavior in previous works with other flavonoids, such as hesperidin, diosmin, and rutin and their oxidovanadium(IV) complexes [21][22][23].…”
Section: Fourier Transformed Infrared Spectroscopymentioning
confidence: 53%
See 1 more Smart Citation
“…Metal-flavonoid chelates have a considerably better biological activity than their flavonoid and metal precursors on their own and we have reported this behavior in previous works with other flavonoids, such as hesperidin, diosmin, and rutin and their oxidovanadium(IV) complexes [21][22][23].…”
Section: Fourier Transformed Infrared Spectroscopymentioning
confidence: 53%
“…It possesses properties such as anti-inflammatory effects [15,16], oxidative stress reduction [17,18], and it has proven to be one potential anticancer agent against different types of cancer and also acted synergistically enhancing the anticancer activities of antitumor drugs in combination therapies [19]. Molecular docking studies showed that naringin interacted with COVID-19 main protease and displayed higher binding affinity than other flavonoids [20] Metal-flavonoid chelates have a considerably better biological activity than their flavonoid and metal precursors on their own and we have reported this behavior in previous works with other flavonoids, such as hesperidin, diosmin, and rutin and their oxidovanadium(IV) complexes [21][22][23].…”
Section: Introductionmentioning
confidence: 78%
“…These results indicated that rutin prenanoemulsion can inhibit A549 lung cancer cells from concentrations higher than 150 μM; pure rutin and the excipients are nontoxic to those cells at concentrations lower than 300 μM. In the study reported by Goitia et al, the cytotoxicity of the complex (Na 2 [VO(rutin)(OH) 2 ]•5H 2 O) in A549 lung cancer cells has the IC50 value of 93 μM [34]. The IC50 value of the complex was lower than the IC50 value of the rutin prenanoemulsion in this study (150 μM).…”
Section: In Vitro Cytotoxicity Of the Rutin Prenanoemulsionmentioning
confidence: 85%
“…Rutin is a naturally occurring bioflavonoid abundantly reported in medicinal herbs, fruits, vegetables, and plant-based beverages. Research has further presented the in vitro potential of rutin in the suppression of numerous human cancers such as lung cancer, prostate cancer, colorectal cancer, breast cancer, liver cancer, glioblastoma, melanoma, osteosarcoma, ovarian cancer, leukemia, cervical cancer, and pancreatic cancer via apoptosis induction, immunity enhancement, or cell migration knockdown, which leads to a significant reduction in the motility rate of cancerous cells [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%